Bible mysteries solving the Bible's greatest mysteries - Bragard, Jean-Claude.; Cox, Anna.; Discovery Channel (firm).; British Broadcasting Corporation (London, UK BBC Worldwide Limited, 2004)
Bible mysteries explores great figures and events from biblical times. Historical, archeological and anthropological evidence gives fresh insights into the historical realities of the times.
Disc 1 (97 min., 33 sec.). Who killed Jesus? ; The real Mary Magdalene -- Disc 2 (96 min., 33 sec.). The disciples ; Peter the rock -- Disc 3 (98 min., 39 sec.). Joseph and his multi-coloured coat ; Joshua and the battle of Jericho -- Disc 4 (97 min., 43 sec.). Revelation : the end of the world? ; David and Goliath ; Herod and the Bethlehem massacre.
Library has: VDR-1577 (1 DVD) ; VDR-1578 (1 DVD) ; VDR-1579 (1 DVD) ; VDR-1580 (1 DVD)
Title from container.
Series producer, Anna Cox ; executive producer, Jean-Claude Bragard.
DVD videos, NTSC Region 3.
In English with subtitles.
Keywords: Bible -- Criticism, interpretation, etc; Bible -- Miscellanea